Sistem Penghitung Stroberi Matang di Kebun berdasarkan Hue dan Saturation menggunakan Algoritme Watershed berbasis Raspberry Pi - Putri Harviana; Hurriyatul Fitriyah; Eko Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Strawberries are fruits that contain many benefits, so strawberries are widely cultivated in Indonesia. In the cultivation, farmers pay attention to the productivity of strawberries in terms of excess quality. Farmers are still counting strawberries conventionally or manually so they ask for a long calculation time. In addition, farmers have never received their harvest now. Therefore, farmers need tools that can help and provide in agriculture known as modern agriculture or modern agriculture. Existing modern agriculture in Indonesia such as rice planting and automatic harvesting equipment, soybean dryers, pesticide sprayers, superior seed sorting machines, and so on. To make a tool that suits the needs of strawberry fruit farmers, researchers developed a mature strawberry counter system in the garden based on hue and saturation values. The hue and saturation values ​​are used because both of these values ​​can overcome the change in light intensity and can be used to detect obsolete strawberries based on the skin color of the fruit. The system uses a watershed algorithm to separate the attached or attached strawberries so that they are counted as different objects. This system is based on Raspberry Pi because it can process images quickly. With this tool it is expected to be used to predict crop yields. The harvest prediction can be used to help the work of farmers in their crops, so farmers can improve the quality of the crop every year. It is hoped that further system development can facilitate farmers to pick strawberries released in the gardens carried out by robots. On the test results obtained by the system, obtained an accuracy rate of 82% with an average calculation time of 7558.1 milliseconds.